Bioengineering of the plant culture of Capsicum frutescens with vanillin synthase gene for the production of vanillin - Chee, Marcus Jenn Yang; Lycett, Grantley W.; Khoo, Teng-Jin; Chin, Chiew Foan (Humana Press, 2016)
Production of vanillin by bioengineering has gained popularity due to consumer demand towards vanillin produced by biological systems. Natural vanillin from vanilla beans is very expensive to produce compared to its synthetic counterpart. Current bioengineering works mainly involve microbial biotechnology. Therefore, alternative means to the current approaches are constantly being explored. This work describes the use of vanillin synthase (VpVAN), to bioconvert ferulic acid to vanillin in a plant system. The VpVAN enzyme had been shown to directly convert ferulic acid and its glucoside into vanillin and its glucoside, respectively. As the ferulic acid precursor and vanillin were found to be the intermediates in the phenylpropanoid biosynthetic pathway of Capsicum species, this work serves as a proof-of-concept for vanillin production using Capsicum frutescens (C. frutescens or hot chili pepper). The cells of C. frutescens were genetically transformed with a codon optimized VpVAN gene via biolistics. Transformed explants were selected and regenerated into callus. Successful integration of the gene cassette into the plant genome was confirmed by polymerase chain reaction. High performance liquid chromatography was used to quantify the phenolic compounds detected in the callus tissues. The vanillin content of transformed calli was 0.057% compared to 0.0003% in untransformed calli.